Exploring the Financial Implications of Advance Rent Payment and Induced Furnishing of Rental Housing in Ghanaian Cities: The Case of Dansoman, Accra-Ghana. Issue 6 (1st November 2020) - Ehwi, Richmond Juvenile; Asante, Lewis Abedi; Morrison, Nicky
ABSTRACT: Across the globe, private rental housing performs a critical role within modern housing systems. However, the nature of the sector, the households it serves, and the contractual landlord–tenant relationships are markedly different. In this article, we explore Ghana's informal rental housing market, which provides accommodation to most renters because of limited housing in the formal housing sector. Drawing on exploratory research and survey data from renters in Dansoman, Accra, we contend that landlords' practice of requiring renters to pay 2 years' advance rent and to furnish their property imposes significant financial burden on the renters. We further demonstrate the extent to which different categories of renters are made worse off by these financial commitments. As government regulatory powers remain weak, private landlords' unscrupulous practices have become an accepted social norm. The younger segments of society that are heavily dependent on this sector are, in particular, made considerably worse off, with knock-on consequences for labor mobility and the ability to create well-functioning housing systems.